Blood glucose threshold determination is stage length dependent - Gilmar de Jesus Esteves; Paulo Eduardo Pereira; Yuri Lopes Motoyama; Mariam Mian Bouchnak; Paulo Henrique Silva Marques de Azevedo (Universidade Estadual Paulista (UNESP), 2020)
Abstract Aim: This study aimed to verify whether different stage length affects the intensity of the Blood Glucose Threshold (BGT), and the agreement between evaluators for BGT determination. Methods: Fourteen subjects attended the laboratory during the first session to perform anthropometric measures and become familiar with procedures. In the following three sessions, subjects performed an incremental test on the ergometer bicycle and in each test a different protocol was performed in randomized order (1, 3- and 5-min stage) to identify BGT. Three different evaluators determined the BGT. Results: Our data show that the BGT is stage length-dependent (1, 3- and 5-min; P<0.0001). The intraclass correlation coefficient showed that there was a strong correlation among evaluators for all protocols (ICC = 0.8 to 1 min; ICC = 0.8 to 3 min; and ICC 0.9 to 5 min). However, one evaluator determined the BGT at a higher intensity than others. The peak load was lower at long stage length. Conclusion: We concluded that stage length influences the BGT intensity determination. The BGT presents a good agreement among evaluators. However, a minimum of two evaluators is needed for BGT determination. The peak load is affected by stage length.